Model Pendidikan Berbasis Komunitas - Toni; Karim, Ajerin; Bahari, Yohanes; Warneri (Tumoutou Social Science Journal, 2024)
The phenomenon of high education costs is a reality that cannot be denied. Currently, education is often considered a "luxury item" that can only be accessed by the rich, while poor people have to wait for luck to get a decent education. The stigma that has developed in society states that quality education is always associated with high costs; The higher the quality, the greater the costs that must be incurred. To implement the concept of community-based education on a campus, it is important to understand its principles, such as liberation, alignment, participation, curriculum that suits needs, evaluation that focuses on students, and self-confidence. This view seeks to eliminate the assumption that building this kind of educational concept must ignore local wisdom. It's time to empower, cultivate and utilize local values in the world of education. This kind of education can be an alternative to empower local communities, especially at SMP Negeri 5 Ledo, Bengkayang Regency, West Kalimantan Province.